Fenologia, biologia floral e germinação in vitro de Cyrtopodium eugenii Rchb. f. & Warm. (Orchidaceae) - NUNES, Camila de Marillac Costa (2009)
Cyrtopodium eugenii Rchb. f. (Orchidaceae) is a specie widely distributed in Brazilian savannah, being the Planalto Central its main center of diversification. C. eugenii is a terrestrial specie, usually found in the Cerrado, growing in sand soil, dry environment and to the half shade. Due the beauty and exotic character of its flowers, C. eugenii present high ornamental and commercial potential. However, no studies were found of its preservation even in vitro protocols for shoots obtainment to be used in flower production. Thus, the present study has as objective to characterize the fenology, morphology and reproductive biology in C. eugenii and to establish protocols for symbiotic and asymbiotic germination in vitro. The plants studied grows at the Biological Reserve Prof. Jose Ângelo Rizzo, a forest remainder of 500 ha of bioma Cerrado, whose predominant vegetation is of the type Cerrado Rupestre, located in the Serra Dourada, city of Mossâmedes-GO. From the months of July of 2007 through August of 2008 monthly visits had been carried out for accompaniment and collects of data of 51 plants, distributed in three populations. For the establishment of the germination protocols in vitro of C. eugenii established the symbiotic culture, pairs the isolated fungic contends the mycorrhizae Epulorhiza sp., obtained from roots of C. eugenii, with the seeds of C. eugenii in medium FA, and the asimbytic culture, where the seeds had been cultivated in culture mediuns that are regularly used for seed orchids germination, being the complete MS medium, the MS medium with reduction to the half of the concentration of macronutrients (½ MS) and the Knudson medium (KC). The analysis of the behavior of C. eugenii allowed to verify that this species present annual budding and at the dry time. At the rainy time, when the temperature raised, plants of C. eugenii start to invest its energy in the production of vegetative parts, such as sprouts of pseudobulbs and leves. The flowers of C. eugenii are disposed of cyclical form in the floral connecting rods, which arrive to reach up to 130 cm of height. This species is self-compatible, even so in natural conditions, the fruit set is low. Not evidenced was presence of efficient pollinators. High frequency of ants during budding of C. eugenii was verified. However, the observations indicated that these insects only act as visitors and they are attracted by the secretion of substance at the time of the budding throughout the floral connecting rod and that have high concentration of soluble solid. The establishment of the symbiotic germination in vitro did not disclose resulted satisfactory because no protocorms formation were obtained. However, satisfactory results had been founded in the asymbiotic germination in vitro, being the ½ MS medium superior to the KC and the complete MS medium for the time, germination of seeds and establishment of new plants of C. eugenii.